Human Cytomegalovirus Antigen Presentation by HLA-DR+ NKG2C+ Adaptive NK Cells Specifically Activates Polyfunctional Effector Memory CD4+ T Lymphocytes - Costa-García, Marcel; Ataya, Michelle; Moraru, Manuela; Vilches, Carlos; López-Botet, Miguel; Muntasell, Aura (Frontiers in Immunology, 2019)
Natural killer (NK) cells play a dual role in the defense against viral pathogens by directly lysing infected cells as well as by regulating anti-viral T cell immunity. Infection by human cytomegalovirus (HCMV) promotes a persistent expansion of NKG2C+ adaptive NK cells which have been shown to display enhanced antibody-dependent responses against infected targets and associated to viral control in transplanted patients. Based on gene expression data showing increased transcription of CIITA and several genes related to the MHC class II pathway in adaptive NK cells, we explored their putative capacity for antigen presentation to CD4+ T cells. Phenotypic analysis confirmed a preferential steady-state expression of HLA-DR by circulating NKG2C+ adaptive NK cells in healthy individuals. Expression of HLA-DR+ in NKG2C+ adaptive NK cells was variable and unrelated to the expression of activation (i.e. CD69 and CD25) or differentiation (i.e. FcRγ chain, CD57) markers, remaining stable over time at the individual level. Incubation of purified NK cells with HCMV complexed with serum specific antibodies induced an up-regulation of surface HLA-DR concomitant to CD16 loss whereas no changes in CD80/CD86 co-stimulatory ligands were detected. In addition, surface CX3CR1 decreased upon antigen-loading while HLA-DR+ NK cells maintained a CCR7-, CXCR3low homing profile. Remarkably, HCMV-loaded purified NK cells activated autologous CD4+ T cells in an HLA-DR dependent manner. The fraction of T lymphocytes activated by antigen-loaded NK cells was smaller than that stimulated by monocyte-derived dendritic cells, corresponding to CD28-negative effector-memory CD4+ T cells with cytotoxic potential. Antigen presentation by NK cells activated a polyfunctional CD4+ T cell response characterized by degranulation (CD107a) and the secretion of Th1 cytokines (IFNγ and TNFα). Overall, our data discloses the capacity of NKG2C+ adaptive NK cells to process and present HCMV antigens to memory CD4+ cytotoxic T cells, directly regulating their response to the viral infection.